Foetal Outcome of among Women Presented with Fetal Head Engagement: Experience of 1440 Cases in Bangladesh (Journal of Current and Advance Medical Research, 2018)
Background: Foetal outcome is a great concern among the primigravida women presented with fetal head engagement.Objectives: The purpose of the present study was to see foetal outcome among the women presented with fetal head engagement.Methodology: This descriptive cohort study was carried out in the Department of Gynecology and Obstetrics at Sir Salimullah Medical College and Mitford Hospital, Dhaka from June 2006 to December 2006 for a period of sic (6) months. Primaigravida women with 38 or more weeks of pregnancy having single foetus with cephalic presentation were selected as study population. Foetal outcome was measured in terms of APGAR score.Result: A total number of 1440 pregnant women were recruited for this study. In this study the APGAR score of all the babies were good. APGAR score were low in l2 cases and returned to normal alter resuscitation. Out of 262 engaged cases 7 to 10 APGAR score was found in 261(99.6%) cases. In 1178 unengaged cases 7 to 10 APGAR score was found in 1167(99.1%) cases. APGAR score 4 to 6 was found in 1 case and 11 cases in engaged and unengaged group. However, 0 to 3 APGAR score was not reported in engaged and unengaged group. There was no statistical significant between the engaged and unengaged group considering the APGAR score of 7 to 10 and 4 to 6 (p=0.374).Conclusion: In conclusion fetal outcome is not significantly different between the engaged and unengaged pregnant women during considering the APGAR score.Journal of Current and Advance Medical Research 2018;5(1):29-32